Effect of doses and administration routes of 9R vaccine on protection of Japanese quails against experimental infection with Salmonella Gallinarum - Nagayoshi, B. A. [UNESP] (2020)
Coturniculture has increased significantly in the last decades. There are several pathogens that can affect these birds. Among the diseases, fowl typhoid stands out as a disease with a potentially great impact to the poultry industry. The objective of this the study was to evaluate the effect of doses and administration routes of live 9R vaccine on protection of Japanese quails against experimental infection with Salmonella Gallinarum (SG). Two hundred and fifty birds were used, divided into five groups: G1, oral vaccination with one dose; G2, oral vaccination with 2 doses; G3, subcutaneous vaccination with one dose; G4, subcutaneous vaccination with two doses and G5 not vaccinated. All birds from all five groups were challenged with SG at an age of 45 days. SG was quantified in the periods of one, four, seven and twelve days after the challenge. The presence of clinical signs and macroscopic lesions of the disease were observed. The groups vaccinated by subcutaneous route had a higher egg production and lower mortality rate. Birds receiving a dose of the vaccine by subcutaneous route also showed lower amount of SG in the liver and spleen seven days after the challenge.